Sustainable Transport for Chinese Cities. - Mackett, R. L. (Roger L) (Transport and sustainability., 2013)
The volume is based on papers presented at a workshop on the green transport agenda and its implications for Chinese cities, organised by the World Conference on Transport Research Society in September 2010.